2008
DOI: 10.1051/m2an:2008019
|View full text |Cite
|
Sign up to set email alerts
|

An entropy satisfying scheme for two-layer shallow water equations with uncoupled treatment

Abstract: Abstract.We consider the system of partial differential equations governing the one-dimensional flow of two superposed immiscible layers of shallow water. The difficulty in this system comes from the coupling terms involving some derivatives of the unknowns that make the system nonconservative, and eventually nonhyperbolic. Due to these terms, a numerical scheme obtained by performing an arbitrary scheme to each layer, and using time-splitting or other similar techniques leads to instabilities in general. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
0
18

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 17 publications
3
75
0
18
Order By: Relevance
“…This example is taken from [4] (see also [31]). The time-splitting scheme proposed there produces a stationary shock (see Figure 7 in [4]), which seems to be unphysical. The solutions computed by our central-upwind scheme on three different grids with ∆x = 1/50, 1/100, and 1/500, do not contain such a shock.…”
Section: Interface Propagationmentioning
confidence: 99%
See 2 more Smart Citations
“…This example is taken from [4] (see also [31]). The time-splitting scheme proposed there produces a stationary shock (see Figure 7 in [4]), which seems to be unphysical. The solutions computed by our central-upwind scheme on three different grids with ∆x = 1/50, 1/100, and 1/500, do not contain such a shock.…”
Section: Interface Propagationmentioning
confidence: 99%
“…An interesting approach to overcome the above difficulties has been recently proposed in [1], where two artificial equations have been added to the system (1.1) so that the extended system becomes hyperbolic and thus could be solved by a second-order Roe-type scheme in a rather straightforward manner. A timesplitting approach, proposed in [4], is another way to implement upwinding without having the full eigenstructure of the system readily available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each layer is assumed to have a constant density, ρ i , i = 1, 2 (ρ 1 < ρ 2 ). The unknowns q i (x, t) and h i (x, t) represent respectively the mass-flow and the thickness of the ith layer at the section of coordinate x at time t. The numerical resolution of two-layer or multilayer shallow water systems has been object of an intense research during the last years: see for instance [1], [3], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [17], [22], [24] . .…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have suggested such models, e.g. LeVeque and Kim [6], Castro and Pares [5], Bouchut and Morales [2] and Audusse [1].…”
Section: Introductionmentioning
confidence: 99%